Socioemotional Wealth and Firms’ Control: Evidence from Malaysian Chinese Owned Companies - Chin Fei Goh; Amran Rasli; Owee Kowang Tan; Sang Long Choi (Gadjah Mada International Journal of Business, 2015)
This paper explores how the preservation of socioemotional wealth can be manifested in the control and corporate governance of Malaysian Chinese firms. Using panel data from the Industrial Products index of the Bursa Malaysia (the Malaysian stock exchange) during 2003-2006, we show that the ingrained ‘life-raft values’ among overseas Chinese entrepreneurs can be associated with the preservation of their socioemotional wealth, and thus they prioritize control over their firms. Additionally, we confirm the monitoring role of non-dominant large shareholders in reducing the families’ influence in managing and enhancing their firms’ performance. Specifically, control contestability exercised by the non-dominant large shareholders mediates the relationship between a family’s involvement in management and their firm’s performance.